Actualization of the Socially Oriented Anti-Value Concept of GREED in Humorous Discourse of the English Linguistic Culture - Arsentiy I. Bochkarev (RUDN Journal of Language Studies, Semiotics and Semantics)
The peculiarities of the comic objectification of the socially oriented anti-value concept GREED are determined by applying an axiological approach consisting of five stages. The article considers the features of comic objectification of the anti-value concept of GREED. The research proves relevant as humorous characteristics of greed have been analyzed in detail. The corpus of the study comprises recordings and scripts of 500 episodes of various sitcoms and more than 70 stand-up specials by American and British writers. Disapproving exclamations accompany laughter periodically while actualizing GREED. In addition, the manifestation of greed is evaluated negatively either by the authors of the sitcoms or by its characters. In humorous discourse the concept is emphasized both manifesting the desire to be wealthy and the desire to save wealth. While the desire of being wealthy is expressed through committing immoral acts in order to achieve wealth and through thieving goods the desire to save wealth is realized either by the unwillingness to share goods with other people or by the priority of wealth over other values. The main sociocultural characteristics that are comically exposed in modern humorous discourse while specifying greed include characteristics of success (rich people), professional characteristics (politicians, bankers, etc.), ethical characteristics (Americans) and gender characteristics (women seeking to get the wealth of the men). The main language means of expressing the analyzed concept in humorous discourse are antithesis and hyperbole. In addition, GREED is mocked through actualizing such concepts as ‘intelligence’, ‘cynicism’, ‘anger’ by a comic addresser.